Palgrave Advances in Charles Dickens Studies
X, 334 p. 7 illus.
Keywords: Palgrave Advances in Charles Dickens Studies is a comprehensive and authoritative guide to the study of one of the most important Victorian novelists. Its editors, Robert L. Patten and John Bowen, are leading authorities on Dickens and the international team of contributors they have assembled contains some of the most exciting critics of nineteenth-century fiction writing today. The book covers the whole range of Dickens's writing and criticism about it, including biographical, theoretical and historical approaches. It is based on up-to-the-minute research and written in a lively and engaging way, and will be essential reading for all students and scholars of this canonical writer.